2019
DOI: 10.1109/access.2019.2936384
|View full text |Cite
|
Sign up to set email alerts
|

Does Providing a Personalized Educational Game Based on Personality Matter? A Case Study

Abstract: While researchers have highlighted the importance of considering learner's personality as a personalization parameter in computer based learning, very few studies have really addressed this parameter in educational games. Therefore, this paper presents an educational game which models learner's personality, specifically introvert/extrovert dimension, to serve as a personalized game learning environment. Fifty one learners were randomly assigned to a control and an experimental group which learned with a nonper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
0
22
1
1
Order By: Relevance
“…Chen and Wang [28] implemented personalized learning on a handheld device to accommodate students with different cognitive styles. Tlili et al [29] developed a personalized educational game based on learners' personalities.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Wang [28] implemented personalized learning on a handheld device to accommodate students with different cognitive styles. Tlili et al [29] developed a personalized educational game based on learners' personalities.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic difficulty adjustment (DDA) [39] is particularly relevant to adapt the challenge to the players' skills or preferences, which may bring an improved game experience [35]. Personality and game experience are related [5]; player types can be found from personality traits, and the latter can be inferred through behavioural data [9], which in turn can help personalise games [16,31]. User modelling from either theoretical frameworks [30], or human domain experts [20], are useful, but have limited flexibility.…”
Section: Related Workmentioning
confidence: 99%
“…In 2019, Ahmed Tlili et al divided 51 learners into a control group and an experimental group, and they learned through the non-personalized version and the personalized version of the game, respectively (Tlili et al, 2019 ). The experimental results showed that personalized educational games not only reduced the cognitive burden of learners, but also allowed learners to show higher perceived usefulness and willingness to use.…”
Section: The Study Value Of Electronic Science Games With Personalization and Adaptationmentioning
confidence: 99%